Atomic Emission Spectrometry AES - Spark, Arc, Laser Excitation - Joosten, Heinz-Gerd (De Gruyter, 2020)
Atomic Emission Spectrometry is a powerful analytical method which is utilized in academia and industry for quantitative and qualitative elemental analysis. This publication is an excellent guide to the technique, explaining the underlying theory and covering practical measurement applications. Extremely well-written and organized, this book is a beneficial instrument for every scientist or professional working with AES.